Peningkatan Pertumbuhan Gereja Melalui Sikap Gembala Jemaat Berdasarkan 1 Petrus 5:2-3 - Yanto Paulus Hermanto (Sekolah Tinggi Teologi Berita Hidup, 2021)
The growth of the church is God's will, so this goal is a priority for God's church. The growth of the church cannot be separated from the character Peter who is a disciple who was asked by the Lord Jesus to shepherd His people. Church growth cannot be separated from the attitude of church leaders (pastors), therefore the problem discussed in this study is how to increase church growth through the attitude of the church pastor based on 1 Peter 5: 2-3. By researching and answering the formulation of this problem, it is hoped that the leaders of the congregation and congregation will have knowledge and attitudes that are in accordance with the word of God, and finally church growth is experienced by all churches.Pertumbuhan gereja merupakan kehendak Allah, sehingga sasaran ini menjadi prioritas bagi gereja Tuhan. Pertumbuhan gereja tidak bisa dipisahkan dari tokoh Petrus yang merupakan murid yang diminta Tuhan Yesus untuk menggembalakan umat-Nya. Pertumbuhan gereja pun tidak dapat dipisahkan dari sikap pemimpin jemaat (gembala), oleh sebab itu masalah yang dibahas dalam penelitian ini adalah bagaimana meningkatkan pertumbuhan gereja melalui sikap gembala jemaat berdasarkan 1 Petrus 5:2-3. Dengan meneliti dan menjawab rumusan masalah ini diharapkan para pemimpin jemaat dan jemaat memiliki pengetahuan dan sikap yang sesuai firman Allah, dan akhirnya pertumbuhan gereja dialami oleh semua gereja.